Assessment of ozone impact on forest vegetation using visible foliar injury, AOT40F exposure index and MDA concentration in two meteorologically contrasting years - Radek Novotný; Leona Vlasáková; Vít Šrámek; Václav Buriánek; Nina Benešová (Journal of Forest Science)
This study aimed to evaluate ozone (O3) phytotoxic potential using AOT40F (accumulated O3 concentration over a threshold of 40 ppb for forest protection), document visible foliar O3 injury across eight forest monitoring plots, analyse MDA (malondialdehyde) content in leaves and needles, and assess the relationship between visible injury and plot conditions. Initial findings are based on data from the 2021 and 2022 vegetation seasons. AOT40F values exceeded the critical level of 5 ppm.h-1 at all plots, with higher values in 2022. The correlation between AOT40F and visible injury was inconsistent; in 2021, minimal visible O3 injuries were observed, while these were more frequent in 2022, notably on Fagus sylvatica leaves. The altitude effect on O3 concentration indicates greater vegetation damage at higher altitudes. In contrast, the AOT40F-altitude relation was not significant. The 2021 vegetation season was characterised by lower temperatures and higher relative air humidity and soil moisture in comparison to 2022. Stomatal conductance conditions were similar in both years, except for lower soil moisture in 2022. Soil moisture, air humidity, and temperature together accounted for about 50% of the variance in visible injury in 2022. The findings suggest that the AOT40F capability for predicting damage to vegetation is limited and highlight the importance of future research focusing on stomatal O3 flux-based approaches.